2014
DOI: 10.1080/07315724.2013.874887
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glycemic Index, Glycemic Load, and Nutritional Correlates in Free-Living Elderly Brazilians: A Population-Based Survey

Abstract: Dietary GI and GL are important indicators of overall quality and quantity of carbohydrates from elderly Brazilians diet and are also associated with other macronutrients such as protein, fat, and fiber. The overall dietary GI and GL reflects other dietary aspects, such as composition of the diet and combination of foods consumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
3
3
0
1
Order By: Relevance
“…For example, a strong positive association with carbohydrate and negative associations with protein, total fat and alcohol have been reported in Western studies ( 6 10 , 13 ) , which are consistent with our present study. However, while Western studies have generally shown a positive association with dietary fibre ( 6 10 ) , with one exception ( 13 ) , we found an inverse association between dietary GL and dietary fibre in our study of Japanese women. This may be due to the much lower intake of whole grains in Japan ( 43 ) .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…For example, a strong positive association with carbohydrate and negative associations with protein, total fat and alcohol have been reported in Western studies ( 6 10 , 13 ) , which are consistent with our present study. However, while Western studies have generally shown a positive association with dietary fibre ( 6 10 ) , with one exception ( 13 ) , we found an inverse association between dietary GL and dietary fibre in our study of Japanese women. This may be due to the much lower intake of whole grains in Japan ( 43 ) .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, associations of dietary GI with intakes of each macronutrient vary across countries. The exceptions to this are protein and dietary fibre, which have consistently shown inverse associations (6)(7)(8)(9)(10)13) , as was also observed in the present study. For carbohydrate, studies in Dutch adults, Spanish men and European non-diabetic populations have shown positive associations (7,8,10) .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations